Antimony modified lithium cobalt oxide material as well as preparation method and application thereof

By wrapping the layer of cobaltate orthopedic materials on the surface of cobaltate, the lithium cobaltate material is formed, and the problem of instability and electrochemical performance attenuation of lithium cobaltate material structure under high voltage under high voltage is solved. performance.

CN119361643AActive Publication Date: 2025-01-24SHENZHEN UNIV

Patent Information

Application Number
CN202411483742.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-24
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

High-voltage lithium cobalt oxide cathode material has problems of structural instability and electrochemical performance attenuation at high voltages, especially at high voltages above 4.5V, the material will undergo multi-scale and multi-dimensional structural changes, resulting in a degradation in performance.

Method used

By wrapping the layer of cobaltate surfaces to form a lithium decorative cobaltate material, the interface stability of the material is enhanced. The material includes lithium cobaltate and wrapped on the surface of its surface, and the layer is composed of pyrine oxidation compounds.

Benefits of technology

The antimony-modified lithium cobalt oxide material exhibits good structural stability and excellent electrochemical performance at a high voltage of 4.65V, including excellent cycle stability and rate performance, and still has a high capacity after 200 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361643A_ABST
    Figure CN119361643A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium ion batteries, and particularly relates to an antimony modified lithium cobalt oxide material as well as a preparation method and application thereof. The antimony modified lithium cobalt oxide material provided by the invention comprises layered lithium cobalt oxide and an antimony layer wrapping the surface of the layered lithium cobalt oxide, the antimony layer includes an antimony oxide compound. The lithium cobalt oxide is wrapped by the antimony layer, so that the interface stability of the lithium cobalt oxide is enhanced, the lithium cobalt oxide has good structural stability under high voltage, and the lithium cobalt oxide has excellent cycling stability and rate capability as a positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries, and specifically relates to an antimony-modified lithium cobalt oxide material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have become an indispensable part of people's lives. The development of high-quality positive electrode materials has become the key to achieving the goal of optimizing the performance of lithium-ion batteries. At present, the progress of 3C (computers, communications and consumer electronics) electronic products, in particular, has put forward higher requirements on the energy density of lithium-ion batteries. As the earliest commercialized positive electrode material, lithium cobalt oxide has a high tap density and a high theoretical capacity (274mAh / g), making it the only choice for positive electrode materials in lithium-ion batteries for portable electronic devices. At present, the commercial market mainly uses 4.45V LiCoO2, whose actual capacity is 180mAh / g, which still has room for improvement compared with its theoretical capacity. Increasing the charging cutoff voltage of lithium cobalt oxide positive electrode has become the preferred way to further increase the capacity of lithium cobalt oxide. In recent years, the academic community has adopted a variety of strategies to improve the performance of high-voltage lithium cobalt oxide (LiCoO2) positive electrode materials, mainly focusing on surface optimization, bulk doping and electrolyte engineering. The academic community generally believes that interface instability and Li in a deep delithiation state are the main reasons for the poor performance of lithium cobalt oxide. + The main problem faced by high-voltage lithium cobalt oxide cathode materials is the undesirable phase transition caused by high-flux diffusion. For example, at over 4.5V (relative to Li / Li + ), lithium cobalt oxide will undergo multi-scale and multi-dimensional structural changes, which involve changes in the bulk and surface, resulting in structural destruction of lithium cobalt oxide and attenuation of electrochemical performance. Therefore, maintaining the structural stability of lithium cobalt oxide at high cut-off voltage is still a problem that needs to be solved urgently. Summary of the invention

[0003] In view of this, the object of the present invention is to provide an antimony-modified lithium cobalt oxide material and a preparation method and application thereof. The antimony-modified lithium cobalt oxide material provided by the present invention has good structural stability under high voltage, so that it has excellent cycle stability and rate performance as a positive electrode material.

[0004] In order to achieve the above object, the present invention provides the following technical solutions:

[0005] The invention provides an antimony-modified lithium cobalt oxide material, comprising layered lithium cobalt oxide and an antimony layer wrapped on the surface of the layered lithium cobalt oxide; the antimony layer comprises an antimony oxide compound.

[0006] Preferably, the thickness of the antimony layer is 1 to 20 nm.

[0007] Preferably, the specific surface area of ​​the antimony-modified lithium cobalt oxide material is 0.2 to 0.5 m 2 / g.

[0008] The present invention also provides a method for preparing the antimony-modified lithium cobalt oxide material described in the above technical solution, comprising the following steps:

[0009] An organic dispersion of lithium cobalt oxide, an organic dispersion of an antimony source and water are mixed, and the antimony source is subjected to a hydrolysis reaction and then dried to obtain a precursor material, wherein the precursor material is lithium cobalt oxide coated with antimony oxide and antimony hydroxide;

[0010] The precursor material is calcined in an oxygen atmosphere to obtain an antimony-modified lithium cobalt oxide material.

[0011] Preferably, the antimony source is one or more of antimony acetate, antimony glycol, antimony trichloride, antimony fluoride and antimony trioxide.

[0012] Preferably, the calcination temperature is 350-450° C. and the calcination holding time is 3-5 h.

[0013] Preferably, the heating rate to the calcination temperature is 3-5°C / min.

[0014] Preferably, after the calcination, annealing is further included; the annealing is cooling from the calcination temperature to room temperature.

[0015] Preferably, the cooling rate is 3-5°C / min.

[0016] The present invention also provides the use of the antimony-modified lithium cobalt oxide material described in the above technical solution or the antimony-modified lithium cobalt oxide material prepared by the preparation method described in the above technical solution as a positive electrode material in a lithium ion battery.

[0017] The present invention provides an antimony-modified lithium cobalt oxide material, comprising a layered lithium cobalt oxide and an antimony layer wrapped on the surface of the layered lithium cobalt oxide; the antimony layer comprises an antimony oxide compound. The present invention uses an antimony layer to wrap the lithium cobalt oxide, thereby enhancing the interface stability of the lithium cobalt oxide, so that the lithium cobalt oxide has good structural stability under high voltage. As a positive electrode material, the lithium cobalt oxide has excellent electrochemical performance (cycle stability and rate performance) under a high voltage of 4.65V, and still has a high capacity after 200 cycles. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The SEM images of the antimony-modified lithium cobalt oxide material (Sb-LCO) and lithium cobalt oxide (LCO) prepared in Example 1;

[0019] Figure 2 XRD patterns of the antimony-modified lithium cobalt oxide material (Sb-LCO) and lithium cobalt oxide (LCO) prepared in Example 1;

[0020] Figure 3This is an EDS image of the antimony-modified lithium cobalt oxide material (Sb-LCO) prepared in Example 1;

[0021] Figure 4 Electrochemical performance diagram of antimony-modified lithium cobalt oxide material (Sb-LCO) and lithium cobalt oxide (LCO) prepared in Example 1;

[0022] Figure 5 Electrochemical performance diagram of antimony-modified lithium cobalt oxide material (Sb-LCO) and lithium cobalt oxide (LCO) prepared in Comparative Example 1;

[0023] Figure 6 Electrochemical performance diagram of antimony-modified lithium cobalt oxide material (Sb-LCO) and lithium cobalt oxide (LCO) prepared in Comparative Example 2;

[0024] Figure 7 This is a rate performance diagram of the antimony-modified lithium cobalt oxide material (Sb-LCO) and lithium cobalt oxide (LCO) prepared in Example 1. DETAILED DESCRIPTION

[0025] The invention provides an antimony-modified lithium cobalt oxide material, comprising layered lithium cobalt oxide and an antimony layer wrapped on the surface of the layered lithium cobalt oxide; the antimony layer comprises an antimony oxide compound.

[0026] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.

[0027] The antimony-modified lithium cobalt oxide material provided by the present invention comprises layered lithium cobalt oxide.

[0028] The antimony-modified lithium cobalt oxide material provided by the present invention comprises an antimony layer wrapped on the surface of the layered lithium cobalt oxide; the antimony layer comprises an antimony oxide compound.

[0029] As an implementation manner, the thickness of the antimony layer in the antimony-modified lithium cobalt oxide material is 1 to 20 nm, and is 10 nm in a specific embodiment.

[0030] As an embodiment, the specific surface area of ​​the antimony-modified lithium cobalt oxide material is 0.2 to 0.5 m 2 / g, in the specific embodiment, 0.3m 2 / g.

[0031] The present invention uses an antimony layer to wrap lithium cobalt oxide, thereby enhancing the interface stability of lithium cobalt oxide and making it have good structural stability under high voltage. As a positive electrode material, it has excellent electrochemical properties (cycle stability and rate performance) under a high voltage of 4.65V, and still has a high capacity after 200 cycles.

[0032] The present invention also provides a method for preparing the antimony-modified lithium cobalt oxide material described in the above technical solution, comprising the following steps:

[0033] An organic dispersion of lithium cobalt oxide, an organic dispersion of an antimony source and water are mixed, and the antimony source is subjected to a hydrolysis reaction and then dried to obtain a precursor material, wherein the precursor material is lithium cobalt oxide coated with antimony oxide and antimony hydroxide;

[0034] The precursor material is calcined in an oxygen atmosphere to obtain an antimony-modified lithium cobalt oxide material.

[0035] The invention mixes an organic dispersion of lithium cobaltate, an organic dispersion of an antimony source and water, performs a hydrolysis reaction on the antimony source, and then dries the mixture to obtain a precursor material, wherein the precursor material is lithium cobaltate coated with antimony oxide and antimony hydroxide.

[0036] As an embodiment, the antimony source is one or more of antimony acetate, antimony glycol, antimony trichloride, antimony fluoride and antimony trioxide. In a specific embodiment, it is antimony acetate, antimony glycol, antimony trichloride, antimony fluoride or antimony trioxide.

[0037] The organic dispersion of lithium cobalt oxide in the present invention is a suspension, and lithium cobalt oxide is not dissolved in anhydrous ethanol. The purpose of the present invention is to evenly stir the lithium cobalt oxide first, so the amount of the organic dispersion added is not particularly limited, and it is only necessary to add an appropriate amount of organic solvent to evenly stir the lithium cobalt oxide in the mixed solution.

[0038] As an embodiment, the preparation method of the organic dispersion of lithium cobalt oxide is: lithium cobalt oxide and anhydrous ethanol are mixed and stirred to obtain the organic dispersion of lithium cobalt oxide. As an embodiment, the stirring rate is 200-500 r / min and the time is 5-20 min; in a specific embodiment, the stirring rate is 300 r / min and the time is 10 min.

[0039] As an implementation manner, the mass percentage of the antimony source in the organic dispersion of the antimony source is 0.8-1%, and in a specific embodiment is 0.8%.

[0040] As an embodiment, the method for preparing the organic dispersion of the antimony source is: mixing the antimony source and the organic solvent and performing ultrasonic treatment to obtain the organic dispersion of the antimony source. As an embodiment, the organic solvent is anhydrous ethanol and / or tartaric acid, the power of the ultrasonic treatment is 300-800W, the frequency is 28-60KHz, and the time is 5-20min; in a specific embodiment, the power of the ultrasonic treatment is 360W, the frequency is 40KHz, and the time is 10min. When the organic solvent is anhydrous ethanol and tartaric acid, the volume ratio of anhydrous ethanol to tartaric acid is 2:1.

[0041] As an implementation mode, the molar ratio of the lithium cobalt oxide to the antimony source is 1:0.0012-0.0028; in a specific embodiment, the molar ratio of the lithium cobalt oxide to the antimony source is 1:0.002.

[0042] As an embodiment, the water is deionized water.

[0043] The purpose of adding deionized water in the present invention is to further promote the hydrolysis of the antimony source. Therefore, the mass of the added deionized water is excessive relative to the antimony source, so there is no need for a specific mass ratio of the antimony source to the water.

[0044] As an embodiment, the organic dispersion of lithium cobalt oxide, the organic dispersion of antimony source and water are mixed as follows: the organic dispersion of antimony source is added dropwise to the organic dispersion of lithium cobalt oxide, and then water is added. As an embodiment, the rate of the dropping is 0.3 to 1 mL / min, and in a specific embodiment is 0.5 mL / min.

[0045] As an implementation mode, the hydrolysis reaction time is 10 minutes to 2 hours; in a specific embodiment, the hydrolysis reaction time is 1 hour.

[0046] As an embodiment, the drying temperature is 40-70°C, the drying is carried out under stirring, and the stirring rate is 200-500r / min; in a specific embodiment, the drying temperature is 50°C, and the stirring rate is 300r / min.

[0047] The present invention has no particular limitation on the drying time, which is until the solvent is evaporated to dryness.

[0048] After obtaining the precursor material, the present invention calcines the precursor material in an oxygen atmosphere to obtain an antimony-modified lithium cobalt oxide material.

[0049] As an embodiment, the purity of the oxygen atmosphere is greater than 99.5%.

[0050] As an implementation mode, the calcination temperature is 350-450°C; the calcination holding time is 3-5h, and the heating rate to the calcination temperature is 3-5°C / min; in a specific embodiment, the calcination temperature is 400°C, the calcination holding time is 5h, and the heating rate to the calcination temperature is 3°C / min.

[0051] As a positive electrode material, there is residual alkali on the surface of lithium cobalt oxide, such as lithium carbonate (Li2CO3), lithium hydroxide (LiOH) or other lithium salts. When the precursor material is antimony oxide and antimony hydroxide coated lithium cobalt oxide, the hydroxide will dehydrate to oxide, and finally form antimony oxide compound after high temperature calcination in oxygen atmosphere.

[0052] As an embodiment, after the calcination, annealing is further included; the annealing is cooling from the calcination temperature to room temperature, and the cooling rate is 3-5°C / min; in a specific embodiment, the cooling rate is 3°C / min.

[0053] The strategy of modifying lithium cobalt oxide on the surface of antimony provided by the present invention is efficient, has a simple synthesis route, and the raw materials are easy to obtain.

[0054] The present invention also provides the use of the antimony-modified lithium cobalt oxide material described in the above technical solution or the antimony-modified lithium cobalt oxide material prepared by the preparation method described in the above technical solution as a positive electrode material in a lithium ion battery.

[0055] The present invention has no special limitation on the application of the antimony-modified lithium cobalt oxide material prepared by the preparation method as a positive electrode material in a lithium-ion battery, and any application method well known in the art can be used.

[0056] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.

[0057] Example 1

[0058] First, 2 g of lithium cobalt oxide was weighed and placed in a beaker, and anhydrous ethanol was added and then placed on a magnetic stirrer and stirred at 300 rpm for 10 min to obtain an organic dispersion of lithium cobalt oxide;

[0059] At the same time, in another beaker, 12.22 mg of antimony acetate was weighed according to 0.2 mol% Sb (the molar ratio of antimony in lithium cobalt oxide and antimony source was 1:0.002), and anhydrous ethanol was added as a solvent, and ultrasonic treatment was performed for 10 min at 25° C., 360 W power, and 40 kHz frequency to obtain an organic solution of antimony acetate (the mass percentage of antimony source was 0.8%);

[0060] The organic solution of antimony acetate is slowly added dropwise to the organic dispersion of lithium cobalt oxide at a rate of 0.5 mL / min, and 5 mL of deionized water is added to promote the hydrolysis reaction of antimony acetate for 60 minutes, and the generated antimony oxide and antimony hydroxide are coated on the lithium cobalt oxide material, and finally a heating jacket is used to continuously stir at 50° C. and 300 r / min until the solvent is evaporated to dryness, thereby obtaining a dry precursor material;

[0061] The precursor material was placed in a tube furnace, heated to 400°C at a heating rate of 3°C / min in an oxygen atmosphere (purity > 99.5%), and calcined at 400°C for 5 hours, and then annealed to room temperature at a rate of 3°C / min to obtain an antimony-modified lithium cobalt oxide material (0.2 mol% Sb-LCO, antimony layer thickness of 10 nm).

[0062] Under this condition, the electrochemical performance (cycle stability and rate performance) of lithium cobalt oxide at 4.65V is optimal.

[0063] Example 2

[0064] The difference from Example 1 is that ethylene glycol antimony is weighed according to 0.2 mol % Sb, the mass percentage of the antimony source in the obtained organic solution of the antimony source is 0.8%, and the antimony-modified lithium cobalt oxide material (Sb-LCO) is obtained.

[0065] Example 3

[0066] The difference from Example 1 is that antimony trichloride is weighed according to 0.2 mol % Sb, the mass percentage of the antimony source in the obtained organic solution of the antimony source is 0.8%, and an antimony-modified lithium cobalt oxide material (Sb-LCO) is obtained.

[0067] Example 4

[0068] The difference from Example 1 is that antimony fluoride is weighed according to 0.2 mol % Sb, the mass percentage of the antimony source in the obtained organic solution of the antimony source is 0.8%, and an antimony-modified lithium cobalt oxide material (Sb-LCO) is obtained.

[0069] Example 5

[0070] The difference from Example 1 is that first, 2 g of lithium cobalt oxide is weighed into a beaker, and a mixed solution of anhydrous ethanol and tartaric acid (the volume ratio of anhydrous ethanol and tartaric acid is 2:1) is added and stirred at a uniform speed to obtain an organic dispersion of lithium cobalt oxide; at the same time, 12.22 mg of antimony acetate is weighed in another beaker according to 0.2 mol% Sb, tartaric acid is added as a solvent, and ultrasonic treatment is performed to obtain an organic solution of antimony acetate (the mass percentage of the antimony source is 0.8%), and an antimony-modified lithium cobalt oxide material (Sb-LCO) is obtained.

[0071] Comparative Example 1

[0072] The difference from Example 1 is that 6.11 mg of antimony acetate is weighed according to 0.1 mol% Sb (the molar ratio of antimony in lithium cobalt oxide and antimony source is 1:0.001), and the mass percentage of antimony source in the obtained organic solution of antimony source is 0.4%, thereby obtaining antimony-modified lithium cobalt oxide material (0.1 mol% Sb-LCO).

[0073] Compared with lithium cobalt oxide, the electrochemical performance of antimony-modified lithium cobalt oxide materials at high voltage is not effectively improved due to the insufficient Sb content under this condition.

[0074] Comparative Example 2

[0075] The difference from Example 1 is that 18.32 mg of antimony acetate is weighed according to 0.3 mol% Sb (the molar ratio of antimony in lithium cobalt oxide and antimony source is 1:0.003), and the mass percentage of antimony source in the obtained antimony source organic solution is 1.2%, thereby obtaining antimony-modified lithium cobalt oxide material (0.3 mol% Sb-LCO).

[0076] Under this condition, the Sb content is too high, resulting in a significant capacity loss of the antimony-modified lithium cobalt oxide material.

[0077] Comparative Example 3

[0078] The difference from Example 1 is that the material is heated to 500° C. at a heating rate of 3° C. / min in an oxygen atmosphere, and calcined at 500° C. for 5 h to obtain an antimony-modified lithium cobalt oxide material.

[0079] Comparative Example 4

[0080] The difference from Example 1 is that the material is heated to 300° C. at a heating rate of 3° C. / min in an oxygen atmosphere, and calcined at 300° C. for 5 h to obtain an antimony-modified lithium cobalt oxide material.

[0081] Performance Testing

[0082] (1) Figure 1 The SEM images of the antimony-modified lithium cobalt oxide material (Sb-LCO) and lithium cobalt oxide (LCO) prepared in Example 1, wherein (a) and (b) are LCO, and (c) and (d) are Sb-LCO. Figure 1 It can be seen that the morphology of Sb-LCO and LCO observed by scanning electron microscopy (SEM) shows that the morphology of the particles remains almost unchanged before and after modification, indicating that surface optimization work will not have an adverse effect on the morphology of the material.

[0083] (2) Figure 2 The XRD patterns of the antimony-modified lithium cobalt oxide material (Sb-LCO) and lithium cobalt oxide (LCO) prepared in Example 1 are shown in FIG. Figure 2 It can be seen that the crystal structures of Sb-LCO and LCO are characterized by XRD. Although the surface optimization strategy is used, the results show that the diffraction peak of Sb-LCO is consistent with that of LCO, indicating that surface optimization has no effect on the bulk structure of Sb-LCO.

[0084] (3) Figure 3 The EDS images of the antimony-modified lithium cobalt oxide material (Sb-LCO) prepared in Example 1, wherein (a) is the SEM image of Sb-LCO, (b) is the O element distribution image of Sb-LCO, (c) is the Co element distribution image of Sb-LCO, and (d) is the Sb element distribution image of Sb-LCO. Figure 3 As can be seen, each figure shows the spatial distribution of a specific element in Sb-LCO.

[0085] (4) Figure 4 The electrochemical performance diagram of the antimony-modified lithium cobalt oxide material (Sb-LCO) and lithium cobalt oxide (LCO) prepared in Example 1. Figure 4 It can be seen that after 100 cycles, the capacity retention rate is 94.14%, and the first cycle capacity is 200.16 mAh / g. This is the electrochemical performance diagram under the optimal conditions.

[0086] (5) Figure 5 The electrochemical performance diagram of the antimony-modified lithium cobalt oxide material (Sb-LCO) and lithium cobalt oxide (LCO) prepared in Comparative Example 1. Figure 5 It can be seen that the content of antimony compound added under this condition is insufficient, and it is not effective enough to improve the electrochemical performance of lithium cobalt oxide at high voltage. After 100 cycles, the capacity retention rate is 85.48%, which is lower than the cycle performance under the optimal conditions.

[0087] (6) Figure 6 The electrochemical performance diagram of the antimony-modified lithium cobalt oxide material (Sb-LCO) and lithium cobalt oxide (LCO) prepared in Comparative Example 2. Figure 6 It can be seen that under this condition, although the capacity retention rate is 96.77% after 100 cycles, due to the excessive content of antimony compound added, the overall capacity is too low, and the first cycle capacity is 192.08 mAh / g, so it is not the best performance.

[0088] (7) Figure 7 The rate performance diagram of the antimony-modified lithium cobalt oxide material (Sb-LCO) and lithium cobalt oxide (LCO) prepared in Example 1. Figure 7 It can be seen that compared with LCO, the rate performance of Sb-LCO has been effectively improved. At a high rate of 10C, Sb-LCO can still show a capacity of 115mAh / g, which is higher than 70mAh / g of LCO.

[0089] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. An antimony-modified lithium cobalt oxide material, characterized in that: It comprises layered lithium cobalt oxide and an antimony layer wrapped on the surface of the layered lithium cobalt oxide; the antimony layer comprises antimony oxide compound.

2. The antimony-modified lithium cobalt oxide material according to claim 1, characterized in that: The thickness of the antimony layer is 1-20 nm.

3. The antimony-modified lithium cobalt oxide material according to claim 1 or 2, characterized in that: The specific surface area of ​​the antimony-modified lithium cobalt oxide material is 0.2 to 0.5 m 2 / g.

4. The method for preparing the antimony-modified lithium cobalt oxide material according to any one of claims 1 to 3, characterized in that: The following steps are involved: An organic dispersion of lithium cobalt oxide, an organic dispersion of an antimony source and water are mixed, and the antimony source is subjected to a hydrolysis reaction and then dried to obtain a precursor material, wherein the precursor material is lithium cobalt oxide coated with antimony oxide and antimony hydroxide; The precursor material is calcined in an oxygen atmosphere to obtain an antimony-modified lithium cobalt oxide material.

5. The preparation method according to claim 4, characterized in that: The antimony source is one or more of antimony acetate, antimony glycol, antimony trichloride, antimony fluoride and antimony trioxide.

6. The preparation method according to claim 4, characterized in that: The calcination temperature is 350-450° C. and the calcination holding time is 3-5 hours.

7. The preparation method according to claim 6, characterized in that: The heating rate to the calcination temperature is 3-5°C / min.

8. The preparation method according to claim 4, characterized in that: After the calcination, annealing is further performed; the annealing is performed by cooling the temperature from the calcination temperature to room temperature.

9. The preparation method according to claim 8, characterized in that: The cooling rate is 3-5°C / min.

10. Use of the antimony-modified lithium cobalt oxide material according to any one of claims 1 to 3 or the antimony-modified lithium cobalt oxide material prepared by the preparation method according to any one of claims 4 to 9 as a positive electrode material in a lithium ion battery.

Citation Information

Patent Citations

  • Lithium titanate cathode material and preparation method thereof and lithium ion battery using lithium titanate cathode material

    CN101944612A

  • Antimony-coated lithium battery positive electrode material and preparation method and application thereof

    CN111682174A

  • Lithium transition metal oxide layered positive electrode material coating surface of antimony compound and preparation method of lithium transition metal oxide layered positive electrode material

    CN113200571A

  • Spinel type positive electrode material, preparation method thereof and lithium ion battery positive plate

    CN114094095A

  • Secondary battery, battery module, battery pack and electric device thereof

    CN115842112A

Cited By

  • Antimony chalcogenide coated lithium cobalt oxide positive electrode material as well as preparation method and application thereof

    CN120328637A

  • Antimony chalcogenide-coated lithium cobalt oxide positive electrode material and its preparation method and application

    CN120328637B